A program that began developing the Nadham structural model using Arduino and its effectiveness in developing Python and task programming skills among high school students - Alqahtani, Amsha Munahi; Al-Turki, Khaled Ibrahim (Journal of Curriculum and Teaching Methodology, 2025)
The study aimed to build a teaching program based on the Needham's constructivist model using the Arduino and to investigate its effectiveness in enhancing Python skills and interactive project programming among high school students. To achieve the study's objective, the researchers employed the experimental method with a quasi-experimental design focused on a single group; to measure the program's effectiveness. The study population consisted of second-year high school female students in the Computer and Engineering track at public schools in Dammam, totaling 61 students. The study tools included a performance test for Python skills and a performance test for interactive project programming skills. After verifying the validity and reliability of the study tools, they were applied to a sample of 35 female students. After collecting the data, processing it statistically, and discussing it to answer the study questions, the following results were obtained: -Effectiveness of the teaching program based on the Needham constructive model using the Arduino in enhancing Python skills, interactive project programming skills among second-year high school students. The study recommended designing professional development programs that focus on constructivist teaching models, such as the Needham model of female teachers, and incorporating modern technologies in teaching and programming instruction with Python, including the use of Arduino. Also utilizing the proposed teaching program based on the constructivist Needham model using the Arduino to enhance female students' programming skills in different grade levels.
Keywords: Internet of Things; Constructivist Theory; C++; Arduino Integrated Development Environment (IDE)